Parenting Practices of Anxious and Non-Anxious Mothers: A Multi-method Multi-informant Approach - Drake, Kelly L. (2011)
Anxious and non-anxious mothers were compared on theoretically derived parenting and family environment variables (i.e., over-control, warmth, criticism, anxious modeling) using multiple informants and methods. Mother-child dyads completed questionnaires about parenting and were observed during an interactional task. Findings revealed that, after controlling for race and child anxiety, maternal anxiety was associated with less warmth and more anxious modeling based on maternal-report. However, maternal anxiety was not related to any parenting domain based on child-report or independent observer (IO) ratings. Findings are discussed in the context of the impact of maternal anxiety on parenting and suggest that child, rather than maternal, anxiety may have a greater influence on parental behavior.